Human resources intelligent selection algorithm with improvement of data validity - Gromov, Aleksey Y.; Petrovskaia, Tatiana A.; Suslina, Anastasia A.; Khizriyeva, Natalia I.; Stepanov, Maxim A. (2018 7th Mediterranean Conference on Embedded Computing (MECO), 2018)
The influence of the intellectual data analysis application in the task of candidates selection for vacancies is investigated. Information analysis in the field of human resource management with increasing reliability of the processed data is proposed. The algorithm uses machine learning approaches and actual principles of human resource management.